2022
DOI: 10.3389/fmolb.2022.919274
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Pan-Cancer Analysis of Senescence With Cancer Prognosis and Immunotherapy

Abstract: Senescence is a double-edged sword in tumorigenesis and affects the immunotherapy response through the modulation of the host’s immune system. However, there is currently a lack of comprehensive analysis of the senescence-related genes (SRGs) in human cancers, and the predictive role of senescence in cancer immunotherapy response has not been explored. The multi-omics approaches were performed in this article to conduct a systematic pan-cancer genomic analysis of SRGs in cancer. In addition, we calculated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
(102 reference statements)
0
0
0
Order By: Relevance
“…Zhao et al. obtained sequencing and clinical information datasets for tumor and normal tissues from the TCGA and the Genotype-Tissue Expression (GTEx) ( 35 ). With the help of ssGSEA, they also obtained their senescence score.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al. obtained sequencing and clinical information datasets for tumor and normal tissues from the TCGA and the Genotype-Tissue Expression (GTEx) ( 35 ). With the help of ssGSEA, they also obtained their senescence score.…”
Section: Discussionmentioning
confidence: 99%
“…The proposal of senescence-related genomes provide data support for further research on the relationship between senescence and tumors. Using senescence-related datasets from the literature, a comprehensive pancancer analysis was conducted (Zhao et al, 2022). The results showed that senescence-related genes are widely different in different cancers and that cell senescence has an important impact on the tumor immune microenvironment.…”
Section: Introductionmentioning
confidence: 99%